Identification and Characterization of Lactic Acid Bacteria (LAB) Isolated from Probiotic Drinks in Malaysia - Wei, Boon Yap; Rina Anak Sujang,; Toong, Seng Tan (Penerbit UKM, 2015)
Many studies have shown that probiotic strains added to a number of probiotic products are not compatible to that of claimed. It is thus of note to validate probiotic strains added to probiotic products. In this study, three probiotic drinks, A, B and C, were cultured on MRS agar and the number of bacterial colonies was enumerated. The bacterial counts recovered from A (9.3 ± 6.9 log CFU/ml) and C (9.0 ± 6.9 log CFU/ml) were signifi cantly higher than B (5.2 ± 3.5 log CFU/ml) and achieved the minimal amount recommended for probiotic bacteria. All of the isolates appeared as gram positive rods microscopically and were proven to be catalase negative. However, there were only A1, A2, B4 and C1 that were highly tolerant to the gastrointestinal pH 3 to 6. The four isolates produced and secreted antimicrobial substances which inhibited the growth of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). C1 showed the greatest growth inhibition by forming 17.50-mm and 17.85-mm inhibition zones against E. coli and S. aureus, respectively. The 16s rDNA sequencing and phylogenetic analysis were performed to further identify the twelve isolates. The twelve isolates were found to be Lactobacillus (L.), particularly L. casei and L. paracasei. However, the bacteria isolated from drink B were incompatible to the labelled ones. In conclusion, probiotic drinks are possible to contain different bacterial counts and probiotic strains from the labelled ones. These differences might affect health benefi ts rendered by probiotic strains to consumers.